Conducting contextual research - Guerin, Bernard, 1957- author.
1 online resource.
Keywords: "This innovative book proposes an entirely new approach to social research, presenting practical ways to discover people's life contexts in order to understand why they do what they do, which is essential for any forms of research that need to understand people. Taking a novel approach that goes beyond traditional categorisations of qualitative and quantitative research, the book starts by discussing the real basis of all research methods in social relationships, before detailing the methods for finding out about a person's life contexts in very practical terms, accompanied by suggested questions, advice, and research tricks to help you progress. The various life contexts are then worked through chapter by chapter. Drawing on the rich and varied research experiences of all the authors, examples are given throughout, with later chapters focusing on specific research areas. Conducting Contextual Research is essential reading for postgraduate students and professionals in the fields of counselling, psychology and social work, and will be useful to anyone conducting research or inquiries to understand human behaviour, including academic researchers, detectives, intelligence operators, social workers, government service researchers, social policy analysts, and biographers"--